Enhanced mechanical properties of polyacrylamide/chitosan hydrogels by tuning the molecular structure of hyperbranched polysiloxane. (15th January 2019) - Li, Shi-Neng; Li, Baoqiang; Gong, Li-Xiu; Yu, Zhi-Ran; Feng, Yujie; Jia, Dechang; Zhou, Yu; Tang, Long-Cheng
Abstract: Hyperbranched polysiloxane (HSi) molecules with tunable molecular structure were synthesized and served as a novel crosslinker for fabricating polyacrylamide/chitosan (PCH) hydrogels. Various characterizations demonstrated that HSi molecules with tunable bi-functional vinyl and epoxy groups were successful prepared and utilized to optimize the network architecture and interactions of polymer chains. Benefiting from the structure of bi-functional crosslinker, PCH hydrogels demonstrated remarkably improved mechanical properties, superior to that of conventional crosslinker or HSi with single vinyl or epoxy group. A tensile strength of 302 kPa, elongation at break of 2263%, and toughness of 3.85 MJ·m –3 can be achieved by optimizing the molecular structure and content of HSi with bi-functional group (e.g. ratio of vinyl/epoxy = 0.68). Additionally, such hydrogels showed outstanding antifatigue ability to withstand cyclic compressive tests. Based on the structure observation and analysis, the improved mechanical properties are likely derived from the combination of homogeneous and strong polymer network and improved interactions of polymer chains (e.g. covalent and hydrogen bonds). Approaches in this study may inspire the design and development of novel crosslinker for fabricating mechanically robust hydrogels. Graphical abstract: Highlights: Hyperbranched polysiloxane (HSi) with tunable molecular structures were designed and synthesized. The polyacrylamide/chitosan hydrogels crosslinked by HSi were fabricated. Benefiting by bi-functional groups of HSi, mechanical properties of hydrogels is superior to that of HSi with single group. The homogenized porous structure and improved interactions of networks contributed to the enhanced mechanical properties.